Definition of a direction of arrival of a signal with the help by the linear aerial of a lattice in a network of mobile communication - Віноградов, М.А.; Правик, Ю.Н. (Proceedings of National Aviation University (archive), 2005)
Are investigated design feature of aerials. The algorithm of definition of a direction of arrival of a signal with the help of a linear lattice of distances between elements (bases) is offered, in large length of a signal Is developed there is a technique of an establishment of aerials of base stations.